2021
DOI: 10.3390/microorganisms9040758
|View full text |Cite
|
Sign up to set email alerts
|

D-Fructose Assimilation and Fermentation by Yeasts Belonging to Saccharomycetes: Rediscovery of Universal Phenotypes and Elucidation of Fructophilic Behaviors in Ambrosiozyma platypodis and Cyberlindnera americana

Abstract: The purpose of this study was to investigate the ability of ascomycetous yeasts to assimilate/ferment d-fructose. This ability of the vast majority of yeasts has long been neglected since the standardization of the methodology around 1950, wherein fructose was excluded from the standard set of physiological properties for characterizing yeast species, despite the ubiquitous presence of fructose in the natural environment. In this study, we examined 388 strains of yeast, mainly belonging to the Saccharomycetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Many fruits have a rich content in sugars and especially in glucose and fructose. Yeasts have the ability to ferment both of these hexoses, with the majority of them showing differential preference in glucose utilization and fermentation, which is associated with the genetic background of the cell [22][23][24]. The reaction rate constant of fructose and glucose fermentation was calculated for each strain (k 1F , k 2F , k 3F , k 1G , k 2G and k 3G ) (Tables 4 and 5).…”
Section: W303-1amentioning
confidence: 99%
“…Many fruits have a rich content in sugars and especially in glucose and fructose. Yeasts have the ability to ferment both of these hexoses, with the majority of them showing differential preference in glucose utilization and fermentation, which is associated with the genetic background of the cell [22][23][24]. The reaction rate constant of fructose and glucose fermentation was calculated for each strain (k 1F , k 2F , k 3F , k 1G , k 2G and k 3G ) (Tables 4 and 5).…”
Section: W303-1amentioning
confidence: 99%
“…Primary fructose consumers identified in this study (closely related or similar species) were shown to (i) harbor enzymatic machinery involved in fructose metabolism (metabolic biochemical fructose pathways referenced in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database), and (ii) other species were already described for their ability to assimilate fructose [ 63 , 64 ]. These observations support our findings and highlight the contribution of these fungi to fructose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed maltose utilization and fermentation of isolated strains using synthetic complete (SC) broth with 2% (w/v) maltose as the sole carbon source, with Durham tubes to capture gas production (Durham, 1898; Endoh et al, 2021). We did not attempt to distinguish among different types of gases produced, although it is likely that gases were dominated by carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%